2019
DOI: 10.1038/s41598-019-46541-w
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale modification of silicon and germanium surfaces exposed to low-energy helium plasma

Abstract: Complex surface nanostructures were observed in germanium and silicon samples exposed to low energy (24 or 36 eV ion kinetic energy) helium plasma. Pyramidal growth is observed in germanium across the temperature range studied (185 °C to 336 °C), while significant modification in silicon was only observed at 630 °C. Nano-wire growth was observed in both germanium and silicon, and appears to be linked to the strength of the electric field, which in turn determines the implantation energy of the helium ions. Nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Recently, to fabricate black silicon, plasma irradiation has been employed with some distinct advantages, such as simple process, economical, and soft for the Si substrate [15,16]. Nonetheless, the morphology and the uniformity of the Si surface are still difficult to control [17][18][19]. Because the reflectance depends on many features of the surface morphology, such as density, size, and height of the nanostructure, it is desired to tailor the morphology with uniformity in a larger area by plasma irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, to fabricate black silicon, plasma irradiation has been employed with some distinct advantages, such as simple process, economical, and soft for the Si substrate [15,16]. Nonetheless, the morphology and the uniformity of the Si surface are still difficult to control [17][18][19]. Because the reflectance depends on many features of the surface morphology, such as density, size, and height of the nanostructure, it is desired to tailor the morphology with uniformity in a larger area by plasma irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…This temperature range was selected, as it is known from past work to produce well‐formed nanostructures. [ 23 ] Temperature measurements were taken early in the exposure before any significant nanostructure formation. Due to the very high heat fluxes in NAGDIS‐II sample, heating was achieved solely through plasma heating.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we focus our attention on a process which utilises a high-flux helium plasma to induce the growth of fine nanoscale surface features in a wide range of materials, including tungsten, [18,19] platinum, [20] silicon [21,22] and germanium. [23] This process is attractive, as it eliminates the need for complex chemical precursors or catalytic seeds that are widely used in other bottom-up fabrication processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that He plasma irradiation leads to the formation of black Si with nanocones on the surface. [29][30][31][32][33] Unlike metals, on Si, whose bandgap is 1.1 eV, He bubbles may not play a major role in the morphological change. Rather, in addition to adatom diffusion, 30) a small amount of impurity deposition formed clusters on the surface and started to form protrusion, leading to the nanocones.…”
Section: Introductionmentioning
confidence: 99%